¿Descentralización en medio de la crisis? - Palacios Lara, Juan José (El Colegio de México A.C., 1989)
This article purports to analyze the descentralization policy established by Mexican President Miguel de la Madrid's administration. In the first part, the need to distinguish between two processes becomes apparent: that of functional decentralization, understood as a virtual process since it does not entail a rearrangement of physical objects within Mexico's national territory and, for that reason, is more feasible and more easy to control; and that of territorial deconcentration, which involves the geographical relocation of physical elements to peripheral areas and which, therefore, is more costly, complex, and difficult to control. In the second part of the article, a brief review is made of the policies and programs carried out in this regard during the period from 1970 to 1982. The third section is devoted to an analysis of the actions and measures put into effects from 1982 to 1988 which, according to the author, follow the same approach, and make use of practically the same instruments that were designed during the previous two six-year administrations. What distinghishes this period is that the efforts were made in the midst of the deepest and longest economic crisis the country has undergone during the post-revolutionary period. Lastly, some remarks are offered concerning the prospects of the decentralizing process given the conditions faced by the present government (of President Carlos Salinas de Gortari).